(untitled) (Communications in Mathematical Research, 2020)
2N+1-soliton solutions of Boussinesq-Burgers equation are obtained by using the Hirota bilinear derivative method and the perturbation technique. Further, we give the graphs of corresponding three- and five-soliton solutions.